ANALISIS PEMEDIASIAN KARIR PLATEAU PADA PENGARUH DUKUNGAN ATASAN DAN KETERLIBATAN KERJA TERHADAP KEPUASAN KERJA - Rushardiono, A.; Priyono, Bambang Suko (Jurnal Ilmiah Telaah Manajemen, 2005)
This study examined the influence of supervisor support, job involvement, and career plateau on job satisfaction. This research tested to employees in PIKA Semarang. The result of this study indicated that the effect of supervisor support, job involvement, and career plateau on job satisfaction were supported, but career plateau as mediating variable was not supported.